Translation and adaptation of self evaluation of listening function and ease of listening form (self+) into Malay version - Yusuf, Nur Hidayah (Universiti Sains Malaysia, 2025)
Hearing loss is a significant global health issue, affecting more than 430 million people worldwide, including a considerable number of children. Early detection and intervention were crucial to reducing the negative effects of hearing impairment on a child’s communication skills, social development, and academic performance. Subjective assessment tools, such as the Self Evaluation of Listening Function and Ease of Listening Form (SELF+), provide valuable insights into children’s listening experiences in everyday situations. However, a validated Malay version of the SELF+ questionnaire was previously unavailable, limiting its use among Malay-speaking populations.This study aimed to translate and culturally adapt the SELF+ into the Malay language for use with Malaysian children aged 7 to 12 years. A cross-sectional design was employed, following a standardized six-step process that included preparation, forward translation, back translation, expert committee review, field testing, and finalization. The validation process involved assessment of content validity by experts.The findings revealed that the Malay version of SELF+ demonstrated strong content validity, with content validity index (CVI) values exceeding the recommended threshold of 0.80. For each item, the Item-level Content Validity Index (I-CVI) for items Q2, Q3, Q4 ,Q6,Q7,Q8,Q9 and Q10 achieved perfect I-CVI scores of 1.00, indicating agreement on clarity and appropriateness. Items such as Q1, Q5, Q11, and Q12 each received I-CVI scores of 0.94, showing strong agreement with minor reservations. The Scale-level Content Validity Index Average (S-CVI/Ave) was 0.98, demonstrating overall excellent clarity across the questionnaire write this in malay version Feedback from children and experts confirmed that the questionnaire items were clear, appropriate, and culturally relevant. The final version was well understood by the target age group. The adapted tool also showed excellent coherence among items, indicating its stability and consistency in assessing listening-related experiences.In conclusion, the Malay version of SELF+ is a valid and reliable tool for evaluating listening function and ease of listening among Malay-speaking children. Its careful cultural and linguistic adaptation makes it a useful instrument for clinicians, educators, and researchers in improving auditory assessments and enhancing hearing healthcare services for children across Malaysia.